Development of and andragogic web site in signed language, using the technical vocabulary employed by Sena in different training programs phase 2 - ANGARITA RODRÍGUEZ, ANGÉLICA MARÍA
Since long time ago, there have been a great breach in the communication process between the hearing people and the population also misnamed deaf-mute. SENA, in the pursuit of not to discriminate against population in learning programs and work placing, has taken as a task the creation of a handbook in sign language with the technical language used by SENA, with the objective of giving access to the different programs to the people with auditory limitation, complying with the law 324 of 1996, in which it is demanded that all institutions either public or private where education or training is imparted, include this population. In this context, Centro Biotecnológico del Caribe presents the basic andragogical handbook of the Colombian sign language and its first pilot applied to the dairy chain. the andragogic concept applied for SENA concerns that people with auditory limitation have popular knowledge and cognitive abilities which are worthy of being part of a productive model of high level. In the development of these strategies, the linguistic and communicative peculiarities of the country’s deaf population are addressed. This lexicographical instrument is the first step towards the standardization of this language, insofar as it reflects the identity and sense of belonging of the Colombian deaf community [4], and it also becomes the first great lexical compendium that facilitates the communicative processes and education of the deaf community of the country, as it constitutes a working tool for teachers, sign language interpreters, linguistic models and other professionals linked in the training processes. It is important to highlight that the development of this web portal and Andragogic Manuals in the different training programs (Technologist in Analysis and development of information systems, Technologist in Food Quality Control, Technologist in Environmental Control, among others), as phase 2 , it is intended to help improve the quality of life of people with this type of limitation, achieving social inclusion in their educational process, since there are many limitations to accessing what they as a population want for their future and this will be achieved improve their social, educational, political and economic status of the deaf communities. The Web Portal and the booklets, in addition to their primary and best-known function of providing information about a language, entail other important social functions such as these.